Thermo thickening behavior of MPEG-b-PCL grafted poly(acrylic acid): a molecular insight - Tiwari, Neha (Polymer, 2018)
We report on the synthesis and characterization of a new thermothickening polymer (PAA-g-(MPEG-b-PCL)) based on the grafting of a block copolymer of mono methoxy poly (ethylene glycol)–b-poly (caprolactone) (MPEG-b-PCL) onto poly (acrylic acid) (PAA). Rheological experiments reveal that aqueous solutions of PAA-g-(MPEG-b-PCL) exhibit interesting irreversible thermothickening behavior above a certain polymer concentration and critical temperature. Light scattering experiments show that increasing temperature induces hydrophobic associations and subsequent aggregation leading to gel formation which is irreversible. The mechanism of thermo thickening was examined at the molecular level by NMR methods which indicated unassembled and assembled environments of the MPEG-b-PCL grafts. On heating, interactions between the graft side chains are significantly enhanced and molecular mobility in the assembled microdomains is reduced. The stable well ordered microdomains that are formed on heating are retained on cooling thus, leading to irreversible gelation.
Keywords: Hydrophobically modified poly (acrylic acid); Light scattering; Methoxy polyethylene glycol-b-polycaprolactone (MPEG-b-PCL) copolymer; Rheology; Thermo gelation

Polymerized stimuli-responsive microgel hybrids of silver nanoparticles as efficient reusable catalyst for reduction reaction - Pany, Biswajit; Majumdar, Amrito Ghosh; Bhat, Suresh; Si, Satybrata; Yamanaka, Junpei; Mohanty, Priti S. (Heliyon, 2024)
We have showcased the potential of polymerized hydrogels (PGMs) with uniform -sized stimuliresponsive microgel particles as promising alternatives to prevent aggregation in solution based nanoparticle systems. In the current work, we implemented the PGM concept by embedding anionic stimuli -responsive microgels (PNIPAM-co-AAc)-silver (Ag) hybrids within a hydrogel matrix. These PGM@AgNP hybrid materials are used as catalysts for the reduction of 4-nitrophenol (4 -NP) to 4-aminophenol (4 -AP) in the presence of sodium borohydride. UV-VIS spectroscopy is used for studying catalytic activity. In the solution based system, the complete reduction of 4NP to 4 -AP took 30 minutes with pure Ag nanoparticles, 24 minutes with PNIPAM-Ag hybrid (Neutral) microgels and 15 minutes with PNIPAM-co-AAc-Ag (Anionic) hybrid microgels. In contrast PGM containing PNIPAM-co-AAc-Ag hybrids achieved full reduction in just 15 minutes, along with a 3 -minute induction period. For pure Ag nanoparticles, the first -order rate constant is found to be 0.25 min - 1, for PNIPAM-Ag hybrid (Neutral), it is 0.21 min- 1 and for PNIPAM-coAAc-Ag (Anionic), it is 0.5 min- 1 where as for PGM containing anionic microgel hybrids it is found to be 0.8 min - 1. Furthermore, the reusability of the PGM-Ag (anionic) materials for catalytic activity remains unaltered even after several washings. In summary, our study highlights the effectiveness of PGM@AgNP materials as efficient catalysts for the reduction of 4-nitrophenol to 4-aminophenol, indicating their versatile potential in various catalytic applications.
Keywords: Light scattering; Microgel-metal hybrids; Nanomaterial catalysts; PNIPAM microgels; Polymerized hydrogel matrix(PGM; Stimuli-responsive microgels